Case Report: Two Newly Diagnosed Patients With KBG Syndrome-Two Different Molecular Changes - Katarzyna Wojciechowska; Joanna Nurzyńska-Flak; Borys Styka; Magdalena Kacprzak; Monika Lejman (Frontiers Media S.A., 2021)
Mutations or deletions of ANKRD11 gene are responsible for the symptoms of KBG syndrome. The KBG syndrome is a rare genetic disorder which is inherited in an autosomal dominant manner. Affected patients usually have characteristic facial features, macrodontia of the upper central incisors, hand abnormalities, developmental delay and short stature. In the present article we would like to report a clinical and molecular case study of two patients affected by KBG syndrome. The diagnosis of the first patient was confirmed by the identification of the novel pathogenic variant in ANKRD11 gene by next-generation sequencing. The second patient was diagnosed after the detection of a 16q24.2q24.3 deletion encompassing the ANKRD11 gene microarray.